Daily analysis in school democratic management (Research, Society and Development, 2020)
The purpose of this paper is to identify the causes of interpersonal conflicts in the school environment. The universe to be researched are 04 school units: 02 schools and 02 (two) day care centers. As for the interviewees were: 02 professionals from each unit. 02 (two) parents or guardians of each Unit, and 02 SME pedagogical advisors. The methods chosen were based on those of the qualitative research, according to Minayo (2010), with an interview script previously selected with questionnaires, containing 05 semi-structured questions, according to the concepts of Lüdke and André (1986). To analyze the collected material, we use content analysis anchored in Bardin (2011). Thus, it was possible to realize that within the conflicts there is a need for the team responsible for this sector to review the methods used to solve the problem. Therefore, it was possible to observe the urgent need for the implementation of existing programs, as well as the creation of new initiatives and projects in the schools of the Cuiabá municipal school that aim to enable, monitor and evaluate new strategies for conflict resolution in the school environment.